(3GdEOGQI GdESJQGJjLjI (B:s (3eaGgje hMGdGJ JWHjbjI (B/s - (3GdSjO, GSeGYjd eMeOs ((3GdEScfOQjI(B: s (3GdecJH GdYQHj GdMOjK(B, s, 1999)
(3GdEOGQI GdESJQGJjLjI(B-(3JMOjO QSGdI GdefXeI hJchjf GdESJQGJjLjI(B-(3GdESJQGJjLjGJ GdHOjdI(B-(3GdENJjGQ GdESJQGJjLj(B-(3hVY GdENJjGQ GdESJQGJjLj ehVY GdJfajP(B-(3Jbjje GdENJjGQ GdESJQGJjLjs
Keywords: (3GdGOGQIs; (3GdGSJQGJjLjIs